Transboundary Pollution Control with Both Production and Consumption Emissions - Shoji Haruna; Rajeev K. Goel (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper adds to the literature on transboundary pollution by considering pollution related to both production and consumption activities. In particular, we consider a symmetric strategic two firm-two country game model with bilateral trade and transboundary pollution to analyze the effects of trade liberalization on economic performance under two types of pollution. Our game-theoretic results with two trading countries find significant differences compared to the case where only production pollution is considered. When trade liberalization policy is mutually implemented, consumer surplus and social environmental damage in the Home and Foreign countries are both increased under production pollution, while they are both decreased under consumption pollution. Furthermore, when the two countries face either production or consumption pollution composed of transboundary pollution and local pollution, consumer surplus, producer surplus, and social environmental damage are larger in the presence of consumption pollution than in the presence of production pollution; and, under certain conditions, social welfare can be larger or smaller in the presence of production pollution than in the presence of consumption pollution. It is uniquely shown that in the three-stage game model trade policy may lose its effectiveness as a policy under consumption pollution. Policy implications are discussed.
Keywords: D43; F13; L13; Q56; 330; environment; transboundary pollution; consumption pollution; production pollution; trade liberalization; environment tax; oligopoly; tariff